Adaptive Reuse Practice Of Teachers’ Quarters In Malaysia - Zulkanain, Mohamad Izzat (2023)
This study intends to (1) investigate the current issues and factors affecting adaptive reuse of teachers’ quarters; (2) identify the management (planning, implementation and monitoring) of teachers’ quarters; (3) identify the adaptive reuse strategy for teachers’ quarters; (4) identify the benefits and challenges of applying adaptive reuse strategy; (5) suggest possible solutions to overcome the challenges of adaptive reuse strategy for unoccupied teachers’ quarters.